2022
DOI: 10.1093/hr/uhac089
|View full text |Cite
|
Sign up to set email alerts
|

Roles of abscisic acid in regulating ripening and quality of strawberry, a model non-climacteric fruit

Abstract: Abscisic acid (ABA) is a dominant regulator of ripening and quality in non-climacteric fruits. Strawberry is regarded as a model non-climacteric fruit due to its extensive genetic studies and proven suitability for transgenic approaches to understand gene function. Strawberry research has contributed to studies on color, flavor development and fruit softening, and in recent years ABA has been established as a core regulator of strawberry fruit ripening, whereas ethylene plays this role in climacteric fruits. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 144 publications
6
36
0
Order By: Relevance
“…With the development of strawberry fruits, the concentration of auxin declined and accelerates the rate of fruit ripening, indicating that auxin content is negatively correlated with fruit ripening. On the contrary, the level of ABA rises at the white stage, and increases rapidly until the red stage, which is consistent with the onset of fruit coloring and anthocyanin accumulation [ 17 , 44 ]. Xu et al showed that MiR167 delayed strawberry fruit senescence by targeting ARF8 under low temperature [ 45 ], the ARF6 and ARF8 single mutation leading to parthenocarpic fruit [ 46 ].…”
Section: Discussionsupporting
confidence: 61%
“…With the development of strawberry fruits, the concentration of auxin declined and accelerates the rate of fruit ripening, indicating that auxin content is negatively correlated with fruit ripening. On the contrary, the level of ABA rises at the white stage, and increases rapidly until the red stage, which is consistent with the onset of fruit coloring and anthocyanin accumulation [ 17 , 44 ]. Xu et al showed that MiR167 delayed strawberry fruit senescence by targeting ARF8 under low temperature [ 45 ], the ARF6 and ARF8 single mutation leading to parthenocarpic fruit [ 46 ].…”
Section: Discussionsupporting
confidence: 61%
“…Abscisic acid plays a pivotal role in regulating the ripening and quality of strawberry fruits ( Jia et al, 2011 ; Li et al, 2022 ). Exogenous ABA treatment promotes AsA accumulation, while the regulatory roles of ABA in this metabolism process have not been well-understood ( Li et al, 2015 , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ethylene is required for ripening initiation in climacteric fruits and is a major cue that initiates most aspects of ripening [ 5 , 32 , 37 ], although signaling by other hormones also augments ripening. In the non-climacteric strawberry, however, ABA appears to be the main initiator of ripening [ 38 ].…”
Section: Erf Transcription Factors In Fruit Ripeningmentioning
confidence: 99%
“…Thus, there is substantial evidence for involvement of ERFs in regulating aspects of ripening in climacteric and non-climacteric fruits. However, it should be emphasized, as mentioned above, that ERFs have been identified mainly by gene homology, and it is possible that in non-climacteric fruit they are regulated by other hormones, in addition to ethylene, such as ABA [ 38 ].…”
Section: Erf Transcription Factors In Fruit Ripeningmentioning
confidence: 99%